Occupational health hazards in street sweepers of Chandrapur city, central India - Priyanka, V. Patil; Kamble, R. K. (International Journal of Environment, 2017)
Street sweepers play an important role in maintaining health and hygiene in cities. They are exposed to road dust and other contaminants while cleaning streets. Exposure of this dust and contaminants irritates respiratory symptoms and airway obstruction. Twenty workers were selected as sample size (10 male and 10 female) and 10 individual as control (5 male and 5 female) for analysis of occupational health hazards in street sweepers of Chandrapur city. The study was carried out from November 2015 to January 2016. Peak Expiratory Flow Rate analysis which was carried out through Breath-o meter and other occupational health hazards through interview schedule specially designed and developed for this study. The results of the study showed that, Peak Expiratory Flow Rate values were lower in exposed workers (sample population) as compared with control group. These workers were exposed to number of environmental and occupational hazards leading to musculoskeletal disorders (100%), respiratory problems (95%), dermatological problems (90%), headache (75%) and gastrointestinal problems (15%) during work. It was further observed that theses workers were suffering from allergies (100%), cough and cold (75%), asthma and bronchitis lungs (65%), hearing disorder (50%), malaria and typhoid (25%), fever (15%) and vomiting (10%) after completion of work. To reduce occupational health hazards in sweepers, they must be made alert and aware of potential health risk arising from their work. Reduction in exposure and use of personal protective equipments should be encouraged.INTERNATIONAL JOURNAL OF ENVIRONMENTVolume-6, Issue-2, Mar-May 2017, Page: 9-18